Structural and computational investigation of an imine-based propeller-shaped macrocyclic cage - Madhu, Suresh; Raghavan, Sriram (SN Applied Sciences, 2021)
In this study, we present the synthesis, spectroscopic and structural characterization of self-assembling gem-dimethyl imine based molecular cage (IMC). Self-assembling macrocycles and cages have well-defined cavities and have extensive functionalities ranging from energy storage, liquid crystals, and catalysts to water splitting photo absorber. IMC has large voids i.e., 25% of the total crystal volume thus could accommodate wide substrates. The synthesized imine-based molecular cages are stabilized by coaxial π bonded networks and long-range periodic van der Waal and non-bonded contacts as observed from the crystal structure. IMC also has typical properties of soft condensed matter materials, hence theoretical prediction of stress and strain tensor along with thermophysical properties were computed on crystal system and were found to be stable. Molecular dynamics revealed IMC is stabilized by, strong interactions between the interstitial phenyl rings. Density functional theory (DFT) based physicochemical properties were evaluated and has band gap of around 2.38ev (520 nm) similar to various photocatalytic band gap materials.